Total Implementation of Management Information Systems on Organizational Performance Improvement - Rudy Usman; Andi Indriani Ibrahim; Yutika Kamerili; Rahmadani Inem Sucakni; Elvira Febriana; Nini Andriani; Moh Fauzan Basalamah (Universitas Muhammadiyah Palu, 2026)
The development of information technology has encouraged organizations to adopt Management Information Systems (MIS) to support decision-making and data management. Effective data management is crucial for producing valuable information for both internal and external organizational purposes. This requires a reliable, integrated, and responsive information system that meets managerial needs. This study aims to evaluate the effect of MIS implementation on organizational performance improvement. Using a qualitative method through a literature review approach, this article analyzes ten relevant scientific journals in the last five years. The results show that the implementation of management information systems contributes positively to operational effectiveness, work efficiency, and organizational productivity. Additionally, supporting factors such as human resource competence, system quality, organizational structure, and user satisfaction also play a crucial role in the success of MIS implementation. Therefore, this study emphasizes the importance of strategic planning and continuous training programs to ensure that MIS can be optimized in enhancing overall organizational performance.